Development of Learning Management Model for Enhancing the Media Production Skills - Chanthra, Rattanaporn; Whattananarong, Krismant; Satienchaiyakij, Paradorn (Rajapark Journal, 2021)
The objectives of this study were 1) to synthesize a learning management model 2) to develop a learning management system for enhancing media production skills and 3) to investigate the use of the developed model. Research and Development. The samples were 38 second-year undergraduate students in Agricultural Education, Faculty of Industrial Education and Technology, King Mongkut's Institute of Technology Ladkrabang, who were enrolled in the course of Media, Innovation, and Information Technology in Education, semester 2, the academic year 2020, selected by using a purposive sampling method. The data was analyzed by using mean, standard deviation, percentage, and t-test statistics. The results showed that 1) the developed model consisted of Action, Active, Application, and Assessment (4A). The model was evaluated by experts at a high level, 2) the learning management was at the highest level, and 3) the results of model implementation indicated the post-study mean score was higher than the pre-study mean score at a significant level of .01, the results of students’ media production were evaluated and indicated that the mean score was 34.63, which was 76.96%. The satisfaction of learners was at a high level. The efficiency of the developed model was 82.93/81.14%, which was higher than the 80/80 criterion. The developed 4A model of learning management could enhance achievement and media production skills.